The Comparison Of Students’ Critical Thinking Skill By The Implementation Of Think Pair Share And Student Teams Achievement Division Cooperative Learning Model In Biology Instruction At SMAN 2 Singaraja - I Wayan Sukra; Ni Luh Putu Manik Widiyanti; Mimin Yeli Sholekah; i gede aris gunadi (Wahana Matematika dan Sains: Jurnal Matematika, Sains, dan Pembelajarannya, 2023)
Critical thinking skills are very useful for students to enter the world of work, so it really needs to be trained in the learning process. This research aims at analyzing the differences of students’ critical thinking skills through implementation of Think Pair Share (TPS) and Student Teams Achievement Division (STAD) Cooperative Learning Models in Biology Instruction at SMA Negeri 2 Singaraja. To achieve that purpose, it has been done a quasi-experiment research which used Nonequivalent Pretest Posttest Control Group Design. The population of this research were all of class XI MIPA (7 classes) at SMA Negeri 2 Singaraja. The research’ samples were class XI MIPA 3 and XI MIPA 4 which is determined by simple random sampling technique by lottery. By these two classes, one class was taught by TPS, there were 32 students. Another one class was taught by STAD, there were 33 students. The data is analyzed by using the descritive analysis and the use of Anacova statistic. By the Anacova testing, it was obtained a statistical value of F = 8,776 with a significance of 0.004. It indicated that (1) there were differences in the critical thinking skills of the students who were taught by TPS with the students who were taught by the STAD and (2) the average value obtained by the group of students who were taught by the TPS cooperative learning model (75.31) was higher than the average value of groups of students who were taught by the STAD cooperative learning model (68.67).